Pertanggungjawaban Pidana Korporasi terhadap Pemalsuan Data Ekspor Zinc Ash yang Dilakukan oleh PT Marakes Jaya Abadi di KPPBC Belawan - Tigor Maruhum Sitorus; Edi Warman; M Citra Ramadhan (Mahesa Research Center, 2021)
This article discusses the legal rules governing corporate liability in laws and regulations against falsification of zinc ash export data, and how the factors that cause zinc ash data falsification by corporations and how the criminal law policies against corporations falsify export data. The method used in this paper is a normative legal research method. Normative legal research is the study of legal materials, both primary legal materials and secondary legal materials. The factors causing the falsification of zinc ash data by corporations are as follows: The factors causing the falsification of customs documents, among others are: (a) Geographic, (b) Production market, (c) Society. Efforts to tackle the crime of falsifying export data by the Belawan Intermediate Customs and Excise Investigation and Customs Enforcement Team (KPPBC TMP) in Belawan have reflected both ways of countermeasures, namely the repressive penal route and the preventive non-penal route.